The Redevelopment of Fairview Slopes in Vancouver, 1975–1995 - Zacharias, John (Urban History Review / Revue d'histoire urbaine, 1997)
Fairview Slopes was almost completely transformed as the political class and the planning and development community focused much of their efforts for a time on this inner city district. While city planning reports in the 1970s were concerned with the preservation of the existing community and the heritage buildings of Fairview Slopes, the redevelopment nevertheless resulted in rapid displacement of the population and replacement of the buildings. This article is concerned with the spatial and temporal patterns of redevelopment. In this case, the redevelopment shows regular temporal and spatial distributions sensitive to topography and location. On the other hand ownership, land use and the distribution of the existing community were relatively unimportant in explaining the distribution of development over time. Municipal regulations introduced at the onset of redevelopment had an important effect on the shape and size of the projects, while redirecting land assembly activity.